ChemInform Abstract: Reactivity Differences of Sc3N@C2n (2n: 68 and 80). Synthesis of the First Methanofullerene Derivatives of Sc3N@D5h—C80. Issue 8 (February 2016) - Ceron, Maira R.; Izquierdo, Marta; Alegret, Nuria; Valdez, Juan A.; Rodriguez‐Fortea, Antonio; Olmstead, Marilyn M.; Balch, Alan L.; Poblet, Josep M.; Echegoyen, Luis
Abstract: Using a purification method introduced earlier based on redox properties, it is possible to isolate Sc3 N@Ih ‐C80 and Sc3 N@D3h ‐C78 and a mixture of Sc3 N@D5h ‐C80 and Sc3 N@D3 ‐C68 .